Probability and Statistics : Concepts and Applications - Beaven, Derek [Ed.] (Willford Press , New York, 2020)
Probability and Statistics are two closely related sub-disciplines of mathematics. Statistics is a mathematical branch that deals with data collection, organization, interpretation, presentation and analysis. There are two main statistical methods used in data analysis - descriptive statistics and inferential statistics. Descriptive statistics summarizes the data from a sample by using indexes like mean and standard deviation, whereas, inferential statistics conclude from data that are subject to random variations. Probability is a measure that quantifies the likelihood that events are going to occur. It measures the quantity as a number between 0 and 1 that respectively indicate the impossibility and certainty of an event. Probability distributions are commonly used for statistical analysis. Both these topics are often studied in conjunction with one another. This book presents researches and studies performed by experts across the globe. It studies, analyzes and upholds the pillars of probability and statistics and their utmost significance in modern times. This book attempts to assist those with a goal of delving into these areas.
Keywords: Probability -- Concepts and Applications; Statistics -- Concepts and Applications